Investigating the story of the appearance of Fazl Loghman in Masnavi and the kingdom that gave bitter fruit to Chakri in Mantiq al-Tair and Rumi's superiority in the artistic development of the story over Attar - Mohamad dost, reza (2021)
In order to critique literary works (comparative literature), the works in question are usually criticized from two different cultures, so according to this type of method, the works created in the same culture can be examined together. He found their commonalities and differences and achieved good results. Although Attar and Sanai have played an important role in determining the intellectual policy and drawing of Rumi's mystical model, Rumi's ability in the art of storytelling and his mystical goals from the results of stories have a high place in literature and educational works, although many stories The works he uses are not in his mind and he has a history in his previous works. (Sanai and Attar) But their goals and final results are different. In this article, an attempt has been made to examine the commonalities and differences of the above story from the perspective of storytelling in order to reveal that Rumi has a higher artistic position than Attar in the art of storytelling.